2017
DOI: 10.1002/pro.3172
|View full text |Cite
|
Sign up to set email alerts
|

Structure of 6‐diazo‐5‐oxo‐norleucine‐bound human gamma‐glutamyl transpeptidase 1, a novel mechanism of inactivation

Abstract: Intense efforts are underway to identify inhibitors of the enzyme gamma-glutamyl transpeptidase 1 (GGT1) which cleaves extracellular gamma-glutamyl compounds and contributes to the pathology of asthma, reperfusion injury and cancer. The glutamate analog, 6-diazo-5-oxo-norleucine (DON), inhibits GGT1. DON also inhibits many essential glutamine metabolizing enzymes rendering it too toxic for use in the clinic as a GGT1 inhibitor. We investigated the molecular mechanism of human GGT1 (hGGT1) inhibition by DON to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 40 publications
4
13
0
Order By: Relevance
“…Enzyme assays were carried out using both human GGT (hGGT) isolated from membranes of human liver cancer cell line HepG2 or chronic B leukemic cells HG3 cells and the commercial equine kidney GGT (eqGGT; with a high percentage of identity with hGGT), maintaining fixed and saturating concentrations of ␥-glutamyl-para-nitroanilide (GpNa) and the acceptor glycyl-glycine (GlyGly) and varying the concentrations of the different testing compounds. Residual GGT activity in the presence of ovothiol A (ovo), isolated from P. lividus eggs in its disulfide form (41), was compared with that in the presence of the trimethyl-2-thiohistidine ergothioneine (erg) stabilized in thione form, the previously characterized GGT inhibitor DON (15), and dithiothreitol (DTT), used as a negative control (Fig. 2).…”
Section: Ovothiol Inhibits Ggt Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Enzyme assays were carried out using both human GGT (hGGT) isolated from membranes of human liver cancer cell line HepG2 or chronic B leukemic cells HG3 cells and the commercial equine kidney GGT (eqGGT; with a high percentage of identity with hGGT), maintaining fixed and saturating concentrations of ␥-glutamyl-para-nitroanilide (GpNa) and the acceptor glycyl-glycine (GlyGly) and varying the concentrations of the different testing compounds. Residual GGT activity in the presence of ovothiol A (ovo), isolated from P. lividus eggs in its disulfide form (41), was compared with that in the presence of the trimethyl-2-thiohistidine ergothioneine (erg) stabilized in thione form, the previously characterized GGT inhibitor DON (15), and dithiothreitol (DTT), used as a negative control (Fig. 2).…”
Section: Ovothiol Inhibits Ggt Activitymentioning
confidence: 99%
“…The most-known compounds that inhibit GGT include glutamine analogues and other amino acidic derivatives such as acivicin, 6-diazo-5-oxo-L-norleucine (DON), azaserine (15,16), sulfur derivatives of L-glutamic acid (17), and ␥-(monophenyl) phosphonoglutamate analogues (18,19). However, most of these compounds have proved to be toxic (20 -22) due to their interference with essential pathways such as the glutamate recycling involved in neurotransmission.…”
mentioning
confidence: 99%
“…Here, we demonstrated that the des-methylated form of ovothiol (5-thio) also acts as a non-competitive-like inhibitor of GGT with Ki values very similar to ovo, and it is non-toxic towards human kidney embryonic cells. Moreover, we proved that both 5-thiohistidines, ovo and 5-thio, act as reversible GGT inhibitors compared to DON, which forms a stable and irreversible DON-GGT complex, consisting of a six-membered ring involving the catalytic Thr381 [31]. These data suggest that 5-thiohistidine derivatives can be finely modulated in in vitro and in vivo studies, thanks to their reversible mode of action.…”
Section: Discussionmentioning
confidence: 61%
“…GGT represents an important enzymatic target for the therapy of a wide variety of pathologies, such as tumors [22][23][24][25], liver fibrosis [17], ischemia/reperfusion-induced renal injury and asthma [26,27], thus the development of inhibitors of this enzyme with high specificity and low toxicity represents a booming field of research. Glutamine analogues have been developed, acting as irreversible competitive inhibitors due to their binding affinity for the donor site, but most of them have been abandoned in clinical trials due to toxicity [30][31][32]. Glutamic acid/glutamate derivatives have been proven to provide a valid therapeutic alternative, as these irreversible GGT inhibitors are more selective and less toxic [33][34][35][36][37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation